Morphological characterization of amaranth (Amaranthus hybridus L.) accessions from urban and peri-urban market gardening in two locations of Côte d’Ivoire - Jean-Claude N’zi; Christophe Kouame; Kabre Vonogo Nikodeme; Fondio Lassina; Edith Agbo; Mahyao Adolphe (European Scientific Journal, ESJ, 2025)
This work focuses on the morphological characterization of eighteen amaranth accessions (Amaranthus hybridus) collected in urban and peri-urban market gardening in Abidjan and Yamoussoukro in Côte d'Ivoire. The accessions have been regenerated and multiplied at the experimental and production station of the National Center for Agronomic Research in Anguédédou. The study was conducted using a Fisher block design with three replicates. Quantitative and qualitative variables were observed and measured for each of these accessions. The results showed a high variability for each of the nine (09) quantitative variables and for some of the fifteen (15) qualitative variables studied. The green morphotype showed the strongest performance in terms of leaf biomass (29 leaves per plant), stem strength (5.9 cm diameter), plant height (137 cm) and panicle length (48.7 cm). These data confirm morphological variability within the population of A. hybridus studied that could be used in a program for the improvement and sustainable cultivation of this foodstuff in Côte d'Ivoire.